Am I my brother's gatekeeper? Professional ethics and the prioritisation of healthcare. Issue 9 (30th August 2007) - Hunter, David
Abstract : At the 5th International Conference on Priorities in Health Care in Wellington, New Zealand, 2004, one resonating theme was that for priority setting to be effective, it has to include clinicians in both decision making and the enforcement of those decisions. There was, however, a disturbing undertone to this theme, namely that doctors, in particular, were unjustifiably thwarting good systems of prioritising scarce healthcare resources. This undertone seems unfair precisely because doctors may, and in some cases do, feel obligated by their professional ethics to remain uninvolved either in deciding priorities and in some cases in enforcing them. I will argue that the professional role of a doctor ought not be considered inconsistent with the role of a priority setter or enforcer, as long as one crucial element is in place, a rationally coherent and broadly justifiable regime for prioritising healthcare. Given this I conclude both that prioritisation and doctoring are not incompatible under certain conditions, and that the education of healthcare professionals ought to include material on distributive justice in healthcare.